Carboxyl Group-Modified Myoglobin Induces TNF-α-Mediated Apoptosis in Leukemia Cells - Yuan-Chin Lee; Jing-Ting Chiou; Liang-Jun Wang; Yi-Jun Shi; Ying-Jung Chen; Long-Sen Chang (MDPI AG, 2022)
Previous studies have shown that chemical modification may increase the activity of proteins or confer novel activity to proteins. Some studies have indicated that myoglobin (Mb) is cytotoxic; however, the underlying mechanisms remain unclear. In this study, we investigated whether chemical modification of the carboxyl group by semicarbazide could promote the Mb cytotoxicity in human leukemia U937 cells and the underlying mechanism of semicarbazide-modified myoglobin (SEM-Mb)-induced U937 cell death. The semicarbazide-modified Mb (SEM-Mb) induced U937 cell apoptosis via the production of cleaved caspase-8 and t-Bid, while silencing of FADD abolished this effect. These findings suggest that SEM-Mb can induce U937 cell death by activating the death receptor-mediated pathway. The SEM-Mb inhibited miR-99a expression, leading to increased NOX4 mRNA and protein expression, which promoted SIRT3 degradation, and, in turn, induced ROS-mediated p38 MAPK phosphorylation. Activated p38 MAPK stimulated miR-29a-dependent tristetraprolin (TTP) mRNA decay. Downregulation of TTP slowed TNF-α mRNA turnover, thereby increasing TNF-α protein expression. The SEM-Mb-induced decrease in cell viability and TNF-α upregulation were alleviated by abrogating the NOX4/SIRT3/ROS/p38 MAPK axis or ectopic expression of TTP. Taken together, our results demonstrated that the NOX4/SIRT3/p38 MAPK/TTP axis induces TNF-α-mediated apoptosis in U937 cells following SEM-Mb treatment. A pathway regulating p38 MAPK-mediated TNF-α expression also explains the cytotoxicity of SEM-Mb in the human leukemia cell lines HL-60, THP-1, K562, Jurkat, and ABT-199-resistant U937. Furthermore, these findings suggest that the carboxyl group-modified Mb is a potential structural template for the generation of tumoricidal proteins.